A comparative evaluation of the shear bond strength of five different orthodontic bonding agents polymerized using halogen and light-emitting diode curing lights: An in vitro investigation - Sujoy Banerjee; Rajlakshmi Banerjee (Wolters Kluwer Medknow Publications, 2011)
Purpose: With the introduction of photosensitive (light-activated) restorative materials in orthodontics, various methods have been suggested to enhance the polymerization of the materials used, including use of more powerful light curing devices. Bond strength is an important property and determines the amount of force delivered and the treatment duration. Many light-cured bonding materials have become popular but it is the need of the hour to determine the bonding agent that is the most efficient and has the desired bond strength. Aim: To evaluate and compare the shear bond strengths of five different orthodontic light cure bonding materials cured with traditional halogen light and low-intensity light-emitting diode (LED) light curing unit. Materials and Methods: 100 human maxillary premolar teeth, extracted for orthodontic purpose, were used to prepare the samples. 100 maxillary stainless steel bicuspid brackets of 0.018 slot of Roth prescription, manufactured by D-tech Company, were bonded to the prepared tooth surfaces of the mounted samples using five different orthodontic bracket bonding light-cured materials, namely, Enlight, Fuji Ortho LC (resin-modified glass ionomer cement), Orthobond LC, Relybond, and Transbond XT. The bond strength was tested on an Instron Universal testing machine (model no. 5582). Results: In Group 1 (halogen group), Enlight showed the highest shear bond strength (16.4 MPa) and Fuji Ortho LC showed the least bond strength (6.59 MPa) (P value 0.000). In Group 2 (LED group), Transbond showed the highest mean shear bond strength (14.6 MPa) and Orthobond LC showed the least mean shear bond strength (6.27 MPa) (P value 0.000). There was no statistically significant difference in the shear bond strength values of all samples cured using either halogen (mean 11.49 MPa) or LED (mean 11.20 MPa), as the P value was 0.713. Conclusion: Polymerization with both halogen and LED resulted in shear bond strength values which were above the clinically acceptable range given by Reynolds. The LED light curing units produced comparable shear bond strength to that of halogen curing units.